Lifestyle intervention discloses an association of the Eating Inventory-51 factors with cardiometabolic health risks - Aldhoon Hainerová, Irena; Zamrazilová, Hana; Hlavatá, Karolína; Gojová, Milena; Kunešová, Marie; Hill, Martin; Nedvídková, Jara; Bellisle, France; Hainer, Vojtěch (Eating and weight disorders, 2013)
Factors of the Eating Inventory-51 (EI) were revealed as significant predictors of health risks. Associations of EI factors (restraint, disinhibition, hunger) with cardiometabolic risk parameters and selected hormones were analysed before and after an in-patient weight reduction programme. Sixty-seven women (age: 48.7 ± 12.2 years; body mass index: 32.4 ± 4.4 kg/m(2)), who exhibited stable weight on a 7 MJ/day diet during the first week, obtained a 4.5 MJ/day diet over the subsequent 3-week period. No significant relations were observed before the weight reduction. After weight loss, restraint score negatively correlated with total cholesterol, fasting blood glucose, C peptide, insulin and neuropeptide Y. Hunger score was positively related to insulin and neuropeptide Y. Disinhibition score correlated positively with lipid profile and neuropeptide Y, while negatively with adiponectin. An implementation of a standard dietary and lifestyle pattern for 3 weeks revealed significant associations between EI factors and metabolic risks in women.
Keywords: hmotnostní úbytek; Adult; Body Weight; lidé středního věku; Body Mass Index; stravovací zvyklosti; složení těla; rizikové faktory; obezita; index tělesné hmotnosti; ženské pohlaví; lidé; Obesity; dospělí; Risk Factors; Life Style; Body Composition; Feeding Behavior; Humans; Weight Loss; tělesná hmotnost; Female; životní styl; redukční dieta; Diet, Reducing; Middle Aged